In Vivo Nutritional Assessment of the Microalga Nannochloropsis gaditana and Evaluation of the Antioxidant and Antiproliferative Capacity of Its Functional Extracts - Rosario Martínez; Alejandro García-Beltrán; Garyfallia Kapravelou; Cristina Mesas; Laura Cabeza; Gloria Perazzoli; Palmira Guarnizo; Alberto Rodríguez-López; Roberto Andrés Vallejo; Milagros Galisteo; Pilar Aranda; Jose Prados; et al. (Marine Drugs, 2022)
Nannochloropsis gaditana is a microalga with interesting nutritional and functional value due to its high content of protein, polyunsaturated fatty acids, and bioactive compounds. However, the hardness of its cell wall prevents accessibility to these components. This work aimed to study the effect of a treatment to increase the fragility of the cell wall on the bioavailability of its nutrients and functional compounds. The antioxidant and antiproliferative capacity of functional extracts from treated and untreated N. gaditana was assessed, and the profile of bioactive compounds was characterized. Furthermore, to study the effect of treatment on its nutrient availability and functional capacity, an in vivo experiment was carried out using a rat experimental model and a 20% dietary inclusion level of microalgae. Functional extracts from treated N. gaditana exhibited higher antioxidant activity than the untreated control. Furthermore, the treated microalga induced hypoglycemic action, higher nitrogen digestibility, and increased hepatic antioxidant activity. In conclusion, N. gaditana has interesting hepatoprotective, antioxidant, and anti-inflammatory potential, thus proving itself an ideal functional food candidate, especially if the microalga is treated to increase the fragility of its cell wall before consumption.